Quantitative microbial ecology off the northern Antarctic Peninsula. Antarctic microbial ecology - Hewes, Christopher D. (Marine Ecology Progress Series, 2010)
The waters surrounding the South Shetland Islands, Antarctica, comprise a coastal/oceanic ecosystem that is iron-fertilized naturally from shelf sources of Weddell Sea origin. My thesis incorporates data from an 18-year time series of hydrographic, chemical and phytoplankton studies carried out during austral summer by the US Antarctic Marine Living Resources program. I show that the South Shetland Islands area is bordered by two contrasting high-nutrient, low-chlorophyll (HNLC) regions, and has an area of phytoplankton blooms that extends eastward from the shelves and shelf breaks surrounding the islands into the central Scotia Sea. As a consequence of low iron concentration, the HNLC region in the northwest sector has low surface chlorophyll concentrations but has a deep chlorophyll maximum (DCM) below the upper mixed layer. The DCM is a result of enhanced production due to elevated iron concentrations in the ferrocline, even though low ambient irradiance (hence light controlled photosynthetic rates) occurs there. The HNLC region in the southeast sector is abundant in nutrients, including iron, but has low chlorophyll concentrations resulting from deeply mixed surface waters to provide low mean ambient irradiances. The phytoplankton blooms in the central and northeast sectors occur where both HNLC sources overlap to result with surface waters having high iron concentrations and shallow mixed layers. This mixing between sources of water is described qualitatively in terms of a salinity gradient, across which the variability in chlorophyll concentration has a unimodal distribution. Maximal concentrations of chlorophyll occur at salinity ~34, and they vary among years as a function of the upper mixed layer depth that is influenced by sea surface temperature. In turn, sea surface temperature appears associated with the atmospheric climate having a global connection through the El Niño Southern Oscillation. The two HNLC areas constitute different biogeochemical provinces, and the phytoplankton community size-class ...